Measuring the European Council agenda: Introducing a new approach and dataset. (March 2014) - Alexandrova, Petya; Carammia, Marcello; Princen, Sebastian; Timmermans, Arco
This article introduces a novel dataset on the agenda of the European Council, the most powerful political body and core informal agenda setter of the EU. Using the approach taken by the Comparative Agendas Project, we trace political issue attention over a 38-year period (1975–2012). The insights in the agenda-setting processes within the European Council shed more light on the overall agenda of the EU and its temporal dynamics. This article explains the construction of the dataset, describes its features, and gives some examples of possible applications.